Determination of Firm Value in the Goods and Consumption Sector - Darmawati Muchtar; Dedek Ramadhani; Rasyimah Rasyimah; Ghazali Syamni (International Journal of Business Economics (IJBE), 2021)
This paper is aimed to examine factors that influence the firm value of goods and consumption companies at IDX.The data used in this study uses data form www.bps.go.id, www.bi.go.idandwww.idx.co.id.The study used a panel data regression model and the random effect model. This study finds that the exchange rate and interest rate have a negative effect on firm value. It can be concluded that external factors have a considerably vast influence on firm value compared to internal factors. Meanwhile, managerial ownership structure and institutional ownership structure have a positive effect on firm value. In relation to company liquidity, a quick ratio solely has a negative effect on firm value.TheNoveltyofthis study shows that companies without managerial ownership have a stronger effect on firm value. Conversely, this study does not find that companies with managerial ownership affect firm value.